Simulating the fluid dynamic behaviour of oar blades in competition rowing - Coppel, A.; Gardner, T. N.; Caplan, N.; Hargreaves, D. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
This study examines the hydrodynamic behaviour of rowing oar blades using computational fluid dynamics (CFD). For initial validation of the modelling technique, the lift and drag coefficients of the Big Blade oar design and a flat rectangular oar were compared against previously published experimental data carried out on quarter-scale blades held stationary at a number of angles of attack to the oncoming flow. The CFD model was in agreement with the experimental data, predicting the lift and drag coefficients within 0.14 and 0.34 of the measured values respectively, although the degree of correlation was found to be sensitive to the particular turbulence model applied. The simulations provided predictions of the fluid-blade propulsive forces of lift and drag over the range of angles of attack used in rowing, and they characterized the features of hydrodynamic flow around the blade. To investigate the performance of currently available oar blades at full scale, a second series of simulations was carried out over a range of blade velocities commonly used in rowing. The CFD model provided much insight into the fluid dynamic behaviour of rowing oar blades and showed great potential as an aid to oar blade design.